(untitled) (Journal of Plant Disease Sciences, 2025)
Basal rot caused by Sclerotium rolfsii is a major constraint in ginger (Zingiber officinale) cultivation, leading to significant yield losses. The present study aimed to isolate and identify the causal organism and evaluate the efficacy of selected fungal and bacterial bioagents against the pathogen under in vitro conditions. The pathogen was isolated from infected ginger rhizomes and identified based on its cultural and morphological characteristics. Pathogenicity was confirmed through rhizome and soil inoculation methods.For bioassay studies, six fungal bioagents—Trichoderma asperellum, Trichoderma harzianum, Trichoderma virens, Aspergillus niger, Metarhizium anisopliae, and Paecilomyces lilacinus—and two bacterial bioagents—Bacillus subtilis and Pseudomonas fluorescens—were tested against S. rolfsii using the dual culture technique.Among all the treatments, Trichoderma asperellum showed the highest antagonistic activity, recording 67.95% inhibition of mycelial growth, followed by T. virens (61.29%) and T. harzianum (54.06%). The bacterial antagonists were found to be ineffective against the pathogen under in vitro conditions. These findings suggest the potential of fungal bioagents, particularly T. asperellum, as effective biocontrol agents against S. rolfsii, offering a sustainable and eco-friendly alternative to chemical fungicides for managing basal rot disease in ginger disease management.